2015
DOI: 10.1111/ppl.12343
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tomato shoot growth by over‐irrigation is linked to nitrogen deficiency and ethylene

Abstract: Although physiological effects of acute flooding have been well studied, chronic effects of suboptimal soil aeration caused by over-irrigation of containerized plants have not, despite its likely commercial significance. By automatically scheduling irrigation according to soil moisture thresholds, effects of over-irrigation on soil properties (oxygen concentration, temperature and moisture), leaf growth, gas exchange, phytohormone [abscisic acid (ABA) and ethylene] relations and nutrient status of tomato (Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 54 publications
4
27
0
Order By: Relevance
“…This is consistent with the research findings that subsurface drainage affected root length density (RLD) along the soil depth [49,50]. In Figure 6a, RLD reached the maximum in the top 20 cm and the minimum in 40-60 cm in all treatments.…”
Section: Responses Of Maize Growthsupporting
confidence: 91%
“…This is consistent with the research findings that subsurface drainage affected root length density (RLD) along the soil depth [49,50]. In Figure 6a, RLD reached the maximum in the top 20 cm and the minimum in 40-60 cm in all treatments.…”
Section: Responses Of Maize Growthsupporting
confidence: 91%
“…As displayed in Figure 6, maize grown in the lysimeters with subsurface drainage had greater root growth as compared to that in CK. This is consistent with the research findings that subsurface drainage affected root length density (RLD) along the soil depth [49,50]. In Figure 6a, RLD reached the maximum in the top 20 cm and the minimum in 40-60 cm in all treatments.…”
Section: Responses Of Maize Growthsupporting
confidence: 91%
“…To describe the temperature response of denitrification, we used Arrhenius equation, which is most commonly used in this case and where the temperature has a stronger effect on the denitrification at lower temperatures [4,47]. Several authors have reported that denitrification has a "breakpoint" temperature, below which denitrification rates decrease more rapidly [9,48,49]. The exact temperature of the breakpoint is not known, but, in most of the studies, it varies usually between 10 and 12 • C [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are endangered subsurface aquifers in the country where growers cannot cover their irrigation water needs from surface water and water saving is a priority in these areas (Biró et al, 2011). Over-irrigation will lead to deep percolation or surface runoff, moreover it can also cause ponding on the surface (Fiebig and Dodd, 2016). Water and energy conservation with a positive impact on crop water productivity and the environment is achievable with site-specific irrigation (Evans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%